High efficiency step-down switched capacitor DC-DC converter - Mohd Syazwan, Rosdi (2010)
The power requirement for vehicles increased continuously in the 20th century as consumers required more from their vehicles; car manufacturers have provided both standard and optional equipment to meet these demands. In addition, during the last 25 years, government legislation for emissions and safety equipment has also added to the power requirements.To solve the power crises in vehicles of the future, a new standard for automotive electrical systems, one based on a voltage, 42V, which is three times higher than used in today’s vehicles is proposed. The need for this higher voltage is being driven by the expectation that automotive electrical loads will continue to rise sharply in the future. Increasing the vehicle voltage will allow the addition of higher power loads without more expensive and heavier wiring. But some loads, such as the existing vehicle lighting, would be better served by 5V. Therefore a possible architecture, 42V power from the main battery is stepped down to 5V by a “High Efficiency Step-Down Switched Capacitor DC-DC Converter”.In this thesis, a prototype “Switched Capacitor Converter” is designed and developed. This converter is capable of supplying 22A at 5V. This converter has an overall efficiency of 80.69%. This prototype can act as a milestone for a better performance, higher power and improve efficiency in tomorrow’s vehicles.